Measuring Piezoelectric Output—Fact or Friction?. Issue 32 (6th July 2020) - Šutka, Andris; Sherrell, Peter C.; Shepelin, Nick A.; Lapčinskis, Linards; Mālnieks, Kaspars; Ellis, Amanda V.
Abstract: Piezoelectric polymers are emerging as exceptionally promising materials for energy harvesting. While the theoretical figures of merit for piezoelectric polymers are comparable to ceramics, the measurement techniques need to be retrofitted to account for the different mechanical properties of the softer polymeric materials. Here, how contact electrification, including friction and contact separation, is often mistaken for piezoelectric charge is examined, and a perspective for how to separate these effects is provided. The state of the literature is assessed, and recommendations are made for clear and simple guidelines in reporting, for both sample geometry and testing methods, to enable accurate determination of piezoelectric figures of merit in polymers. Such improvements will allow an understanding of what types of material manipulation are required in order to enhance the piezoelectric output from polymers and enable the next generation of polymer energy harvester design. Abstract : Enhancing the energy‐harvesting capabilities of piezoelectric polymers is a key challenge for next‐generation wearable and remote technologies. Achieving this enhancement is challenging, and many literature reports confuse charge arising from contact electrification or triboelectricity with the piezoelectric effect. A simple solution is provided for the avoidance of this confusion with a framework enabling a robust literature discussion about the field moving forward.